Pathology Full Circle: A History of Anti-Vibrator Legislation in the United States - Lindemann, Danielle J. (Columbia Journal of Gender and Law, 2006)
In The Technology of Orgasm, Rachel Maines traces the electromechanical vibrator back to its inception in the late 1800s, when it was employed solely by medical professionals who sought to relieve symptoms of hysteria and various other ailments in their female patients. For several decades, the vibrator remained largely uncontroversial, even when it began appearing outside the confines of the doctor’s office and in private homes, because it was consistently marketed as a medical-and not overtly sexual–device. After it began appearing as an instrument of sexual pleasure in pornographic films of the 1920s, the vibrator’s primary function became impossible to deny, and it essentially disappeared from public (though not private) life until the 1960s, when it emerged in advertisements as an explicitly sexual commodity. Maines, however, fails to explore extensively either contemporary attitudes towards the vibrator or its current status as a medical or pleasurable instrument. This Article picks up where Maines leaves off, arguing that a modem-day legal emphasis on the vibrator’s use as a treatment for female sexual dysfunction and the contemporary courts’ repeated attestations that the device’s worth lies in its therapeutic value bring us full-circle to an era when the device was legitimated only as a treatment. Part I describes the historical background of the vibrator up until the 1960s. Part H summarizes anti-vibrator legislation that has emerged in recent years in several states. Part In examines contemporary medical and therapeutic arguments advanced by plaintiffs who have been prosecuted for the sale of sex toys. Legislation to prohibit the distribution of the device in several states has been combated by arguments that have overwhelmingly emphasized the vibrator’s efficacy as a therapeutic tool for anorgasmic women and women with other sexual “dysfunctions.” This section posits that these defense